Perturbed actin cap as a new personalized biomarker in primary fibroblasts of Huntington’s disease patients - Gharaba, Saja; Paz, Omri; Feld, Lea; Abashidze, Anastasia; Weinrab, Maydan; Muchtar, Noam; Baransi, Adam; Shalem, Aviv; Sprecher, Uri; Wolf, Lior; Wolfenson, Haguy; Weil, Miguel (Frontiers in Cell and Developmental Biology, 2023)
Primary fibroblasts from patient's skin biopsies are directly isolated without any alteration in the genome, retaining in culture conditions their endogenous cellular characteristics and biochemical properties. The aim of this study was to identify a distinctive cell phenotype for potential drug evaluation in fibroblasts from Huntington’s Disease (HD) patients, using image-based high content analysis. We show that HD fibroblasts have a distinctive nuclear morphology associated with a nuclear actin cap deficiency. This in turn affects cell motility in a similar manner to fibroblasts from Hutchinson-Gilford progeria syndrome (HGPS) patients used as known actin cap deficient cells. Moreover, treatment of the HD cells with either Latrunculin B, used to disrupt actin cap formation, or the antioxidant agent Mitoquinone, used to improve mitochondrial activity, show expected opposite effects on actin cap associated morphological features and cell motility. Deep data analysis allows strong cluster classification within HD cells according to patients’ disease severity score which is distinct from HGPS and matching controls supporting that actin cap is a biomarker in HD patients' cells that could be modulated by pharmacological agents as tool for personalized drug evaluation.